Plant relationships - Esser, K,, Ed (Mycota ;, 2009)
Since the publication of the first edition of "The Mycota Vol. V - Plant Relationships" in 1997, tremendous advances in fungal molecular biology and biochemistry have taken place; and both light and electron microscopical techniques have improved considerably. These new insights led to a better understanding of the relationships between fungi and plants; and a completely revised new edition of Plant Relationships could be produced, providing an up-to-date overview on mutualistic and pathogenic interactions. In 18 chapters internationally acknowledged authors present reviews on fungal lifestyles, mechanisms of their interactions with their host plants, signal perception and transduction, and plant defense responses directed against attack by fungal pathogens. Highlighting the recent developments in fungus-plant interactions, this volume is indispensable for researchers, lecturers and students in microbiology, mycology and plant sciences, including plant pathology.